Effects of strength training on neuromuscular adaptations in the development of maximal strength: a systematic review and meta-analysis - Wenchao, Rong; Soh, Kim Geok; Samsudin, Shamsulariffin; Yue, Zhao; Hucheng, Ma; Xinrui, Zhang (Nature Research, 2025)
A systematic review of the effects of resistance training on neuromuscular adaptations related to maximal strength enhances our understanding of the mechanisms and dose–response relationships involved. This evidence supports the scientific application of maximal strength to improve athletic performance in practice. Methods: We retrieved literature from CNKI, PubMed, and Web of Science databases. We utilised Review Manager 5.4.1 software to construct forest plots and assess methodological quality based on the standards outlined in the Cochrane Handbook for Systematic Reviews of Interventions (version 5.1.0). Review Manager 5.3 was employed to analyse the outcome measures of the included studies. Given that the outcome measures were continuous variables, we chose the standardised mean difference (SMD) as the effect size metric for statistical analysis. We used Stata-SE 18.0 to conduct publication bias analysis. Results: Twenty studies examined the relationship between resistance training and maximal skeletal muscle strength, revealing low heterogeneity (I2 = 17%, P = 0.24). The results indicated an SMD of 0.77 (95% CI 0.57–0.98, P < 0.05), demonstrating a significant effect. The publication bias test yielded t = 4.12 (P < 0.05). Fifty-four studies examined the relationship between resistance training and peak torque, revealing moderate heterogeneity (I2 = 48%, P < 0.05). The results indicated an SMD of 0.77 (95% CI 0.62–0.93, P < 0.05), demonstrating a significant difference. The publication bias test yielded t = 6.69 (P < 0.05). Eighteen studies examined the relationship between resistance training and the percentages of Type I, Type IIa, and Type IIx muscle fibres, revealing significant moderate heterogeneity (I2 = 85%, P < 0.05). The results indicated an SMD of 0.14 (95% CI − 0.45–0.74, P = 0.63). The publication bias test yielded z = 3.62 (P < 0.05). Forty-one studies examined the relationship between resistance training and muscle thickness, revealing no heterogeneity (I2 = 0%, P = 0.80). The results indicated that resistance training programs significantly increase participants’ skeletal muscle thickness (SMD = 0.55, 95% CI 0.41–0.69, P < 0.05). The publication bias test yielded z = 2.09 (P < 0.05). Ten studies examined the relationship between resistance training and pennation angle, revealing moderate heterogeneity (I2 = 54%, P < 0.05). The results indicated an SMD of 0.36 (95% CI − 0.02–0.74, P = 0.06). The publication bias test yielded z = − 2.71 (P < 0.05). Twenty-eight studies examined the relationship between resistance training and EMG, revealing moderate heterogeneity (I2 = 58%, P < 0.05). The results indicated that resistance training programs significantly increase participants’ squat strength (SMD = 0.54, 95% CI 0.26–0.81, P < 0.05). The publication bias test yielded z = 5.62 (P < 0.05). Maximal resistance training enhances maximum strength and peak torque in bench presses and squats. Muscle adaptations include increased agonist muscle thickness, a higher proportion of Type I and Type IIa fibres, a reduction in Type IIx fibres, and an increase in pennation angle. Neural adaptations are reflected in heightened EMG amplitude, though the effect size varies with muscle contraction type and training experience. Physiologically, maximal resistance training activates satellite cells and the mTOR signalling pathway, contributing to muscle repair, hypertrophy, and strength improvement.